HAK SISTEM PEMILIKAN TANAH BANGSA INDONESIA DAN KAITANNYA DENGAN PENERAPAN HAK-HAK DERIVATIF DALAM RANGKA AGUNAN UTANG-PIUTANG - Aslan Noor (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2015)
Law No.4 of 1996 is the mandate of Article 51 of Law No. 5 of 1960, which regulates the only institution security rights over the landknown as Mortgage. The law completes the realization of law unification in the field of national land management .The existance of the law bring fresh air for business development in Indonesia. Land and buildings located on it can be used as collateral either by the individual or legal berau. As it can raise fund sasinitial capitalin doing business (business activity) to sustain the economy and national development.